Surface‐bound orientated Jagged‐1 enhances osteogenic differentiation of human periodontal ligament‐derived mesenchymal stem cells1. Issue 2 (30th July 2012) - Osathanon, Thanaphum; Ritprajak, Patcharee; Nowwarote, Nunthawan; Manokawinchoke, Jeeranan; Giachelli, Cecilia; Pavasant, Prasit
Abstract: Notch signaling plays critical roles in various cell types by regulating cell fate determination and differentiation. Here, we investigated the ability to control differentiation of human periodontal ligament derived mesenchymal stem cells using modified surfaces containing the affinity immobilized Notch ligand, Jagged‐1. After seeding human periodontal ligament derived mesenchymal stem cells (HPDLs) on Jagged‐1 modified surfaces, expression of Notch signaling target genes, Hes‐1 and Hey‐1, was higher than those exposed to soluble Jagged‐1 or control surfaces. Upregulation of Notch signaling target genes was attenuated after treatment with the γ secretase inhibitor. Upon seeding the cells on Jagged‐1 immobilized surface and maintained in osteogenic medium, alkaline phosphatase enzymatic activity and mineralization as well as mRNA expression of alkaline phosphatase (ALP), collagen type I (COL I) and osteopontin (OPN) were significantly increased compared to those of controls. However, osteocalcin (OCN) mRNA expression level was decreased when cells were exposed to Jagged‐1 modified surfaces. HPDLs on Jagged‐1 modified surfaces expressed lower TWIST2 mRNA levels than the control, suggesting that the mechanism whereby Jagged‐1 enhances osteogenic differentiation of HPDLs may occur through Notch signaling and TWIST regulation. In summary, an alteration of biomaterial interface using Notch ligands illustrates a promising system to control HPDLs differentiation toward osteogenic lineage. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2013.